Differential Pulse Anodic Stripping Voltammetric Analysis for Determination Selenium (IV) in Bulk and in Dosage Formulations Using Multi-Modified Gold Electrode With a Mixture of O-Phenylenediamine and 2,3-Diaminonaphthalene-Nafion (JOURNAL OF ADVANCES IN CHEMISTRY, 2018)
The effect of gold electrode modified with 2,3-Diaminonaphthalene (GEMDANN) or multi-modified or a mixture 2,3-diaminonaphthalene and o-phenylenediamine -nafion (GEMDAN-OPDAN) on determination of selenium (IV) using differential pulse anodic stripping voltammetric analysis (DPASVA) has been studied. Various parameters (electrolyte, deposition time, pulse duration, pulse amplitude, etc.) are affecting determination of the Se(IV) in HClO4 (0.2 M) at pH 0.22 were examined. Under the optimum conditions, liner calibration graph, Ip=f(CSe4+), were obtained in the concentration ranges of 5x10-8 - 1x10-6 M (3.948 -78.96 ng.mL-1 ) with relative standard deviations (RSD) 4.2% and detection limit 0.056 ng.mL-1, and 1x10-9 -1x10-6 M (0.07896 -78.96 ng.mL-1 ) with relative standard deviations (RSD) 4.9% and detection limit was 0.014 ng.mL-1 on GEMDANN and GEMDAN-OPDAN, respectively. This method showed a good accumulation efficiency for selenium and good resistance to interferences from metal ions as well as those associated with selenium in pharmaceuticals. The results for the determination of Se4+ using GEMDAN-OPDAN (multi-modified) were more sensitive (about 50 times) than that obtained using GEMDANN.